FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KADER POSYANDU TERHADAP PERCEPATAN PENURUNAN STUNTING: Studi di Wilayah Kerja Puskesmas Sungai Durian Kabupaten Kubu Raya, Provinsi Kalimantan Barat - Ita, Margaretha; Kosasih, Kosasih; Utoyo, Widjajanti (Jurnal Manajemen Kesehatan Indonesia, 2024)
Stunting is a condition where a child fails to grow properly during the first 1000 days of life due to long-term malnutrition. This research aim is to identify the factors (Knowledge, Motivation, Training, Attitude) that affect the performance of posyandu cadres in accelerating Stunting reduction within the Sungai Durian Health Center work area, using quantitative research methods with descriptive and verification analysis. The results of the descriptive analysis showed that knowledge had an excellent average score of 4.03, motivation had a good average score of 3.66, training had a good average score of 3.80, and attitudes had a good average score of 3.76. Based on the T count and T table results, knowledge influenced with a score of 6.642 > 2.023, motivation with a score of 4.287 > 2.023, training with a score of 2.598 > 2.023, and attitudes with a score of 3.652 > 2.023. Means there is an influence based on the results of the T test the most influence factor is knowledge on accelerating Stunting reduction. The F test showed that the performance factors of posyandu cadres, which are knowledge, motivation, training, and attitudes, collectively affect the acceleration of Stunting reduction, with an F count score of (752.317 > 2.61). The significance of the F score was 0.000, and the R Square value was 0.893, meaning that 89.3% of the independent variables were bound, while the remaining 10.7% was influenced by other variables that were not included in this research model.